Task-Layer Multiplicity as a Measure of Community Level Health. (1st July 2019) - Fraundorf, P.
Abstract : The insights of many disciplines, and of commonsense, about individual-level well-being might be strengthened by a shift in focus to community-level well-being in a way that respects belief systems as well as the power of each individual. We start with the jargon of complex systems and the possibility that a small number of broken symmetries, marked by the edges of a hierarchical series of physical subsystem types, underlie the delicate correlation-based complexity of life on our planet's surface. We show that an information-theory-inspired model of attention-focus on correlation layers, which looks in/out from the boundaries of skin, family, and culture, predicts that behaviorally diverse communities may tend toward a characteristic task-layer multiplicity per individual of only e 29/20 ≅ 4.26 of the six correlation layers that comprise that community. This behavioral measure of opportunity may help us to (i) go beyond GDP in quantifying the impact of policy changes and disasters, (ii) manage electronic idea-streams in ways that strengthen community networks, and (iii) leverage our paleolithic shortcomings toward the enhancement of community-level task-layer diversity. Empirical methods for acquiring task-layer multiplicity data are in their infancy, although for human communities a great deal of potential lies in the analysis of web searches and asynchronous experience sampling similar to that used by "flu near you."